HMGB1 Protects the Heart Against Ischemia–Reperfusion Injury via PI3K/AkT Pathway-Mediated Upregulation of VEGF Expression - Zhou, Yan-Hong; Han, Qian-Feng; Gao, Lei; Sun, Ying; Tang, Zhan-Wei; Wang, Meng; Wang, Wei; Yao, Heng-Chen (Frontiers in Physiology, 2020)
Exogenous high mobility group box 1 (HMGB1) may exert beneficial effect on myocardial ischemia reperfusion (I/R) injury. It was previously proven that myocardial expression of vascular endothelial growth factor (VEGF) and phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) are related to the cardioprotective effects of basic fibroblast growth factor. So, we hypothesized that intravenous HMGB1 may protect myocardium from I/R injury via increases the myocardial expression of VEGF through the activation of PI3K/Akt pathway. Thus, the purpose of the present study was to investigate the effects of intravenous HMGB1 on the myocardial expression of VEGF, myocardial fibrosis and cardiac function in rats following acute myocardial ischemia. Myocardial ischemia was induced by temporary (30 min) ligation of the left anterior descending coronary artery in sham or HMGB1 treated rats, followed by a 3-h reperfusion. Myocardial MDA content, Infarct size and myocardial CVF decreased while the SOD activity, expression of VEGF and p-Akt protein were significantly increased in HMGB1 treated group than in the I/R group (all P <0.05). Cardiac function was improved after HMGB1 pretreatment. However, all the above-mentioned effects of HMGB1 was abolished by LY294002. These results that intravenously pre-treatment with HMGB1 may exert its cardioprotective effects via upregulates the myocardial expression of VEGF which may be regulated by PI3K/Akt signal pathway in myocardial I/R rats.